FACTORS AFFECTING JOB INVOLVEMENT OF TEACHERS UNDER THE OFFICE OF PRACHINBURI PRIMARY EDUCATIONAL SERVICE AREA II - วงศ์เพ็ชร อรทัย; คนฉลาด คุณวุฒิ; งามกนก สุเมธ (Journal of Educational Review Faculty of Education in MCU, 2019)
The purposes of this research were to study the factors that affects the job involvement of the teachers under the office of Prachinburi Primary Educational Service Area II by studying the level of the quality of worklife and the job involvement of the government teachers. The reserch studied the levels of these factors; gender, educational qualification, income, school sizes, and quality of work life affecting the job involvement of the teachers. The research also aimed to create the predictive equation of the job involvement of teachers under the Office of Prachinburi Primary Educational Service Area II regarding gender, educational qualification, income, school sizes, and quality of work life.The research sample was 263 teachers under the office of Prachinburi Primary Educational Service Area II in the academic year 2015. The research instruments were a questionnaire on the teachers’ status with a five level rating scales questionnaire. Statistics used in data analysis included mean (), Standard Deviation (SD), Simple Correlation, and Stepwise multiple regression analysis. The research results were: 1. The overall mean of the teachers’ quality of work life was at a high level. When considering each aspect it was, found that each aspect was at a high level. The three highest aspects were, Constitutionalism in work, Social relationship, Fair and sufficient compensation. 2. The overall mean of the job involvement of the teachers was at a high level. When Considered each aspect, it was found that each aspect was at a high level. The three highest aspects were, ‘they are pleased to help colleagues when problems occur.’, ‘they will work over-time to finish work, even if you they not paid.’, and ‘they never feel discouraged when they encounter problems and obstacles at work. 3. The job involvement of the teachers under the office of Prachinburi Primary Educational Service Area II in overall and each aspect were positively related statistically significant at .05 level. 4. The best factors of predictive equation of the job involvement of teachers was found to be the woman aspect variable and income aspect variable which can predict the job involvement of the government teachers in overall 71.70 percents and can predict the job involvement of the teachers statistically significant at 0.5 level. The raw acore equation was as follow.